Multidimensional protein characterisation using microfluidic post-column analysis. Issue 15 (26th June 2020) - Scheidt, Tom; Kartanas, Tadas; Peter, Quentin; Schneider, Matthias M.; Saar, Kadi L.; Müller, Thomas; Challa, Pavan Kumar; Levin, Aviad; Devenish, Sean; Knowles, Tuomas P. J.
Abstract : Direct combination of liquid chromatography with multidimensional post-column analysis through microfluidics for individual quantification of biophysical parameters. Abstract : The biological function of proteins is dictated by the formation of supra-molecular complexes that act as the basic machinery of the cell. As such, measuring the properties of protein species in heterogeneous mixtures is of key importance for understanding the molecular basis of biological function. Here, we describe the combination of analytical microfluidic tools with liquid chromatography for multidimensional characterisation of biomolecules in complex mixtures in the solution phase. Following chromatographic separation, a small fraction of the flow-through is distributed to multiple microfluidic devices for analysis. The microfluidic device developed here allows the simultaneous determination of the hydrodynamic radius, electrophoretic mobility, effective molecular charge and isoelectric point of isolated protein species. We demonstrate the operation principle of this approach with a mixture of three unlabelled model proteins varying in size and charge. We further extend the analytical potential of the presented approach by analysing a mixture of interacting streptavidin with biotinylated BSA and fluorophores, which form a mixture of stable complexes with diverse biophysical properties and stoichiometries. The presented microfluidic device positioned in-line with liquid chromatography presents an advanced tool for characterising multidimensional physical properties of proteins in biological samples to further understand the assembly/disassembly mechanism of proteins and the nature of complex mixtures.